Quest for Identity and Self- Reclaiming as Shown in Laurie Halse Anderson’s Speak - Kadhim Hussein, Nada (Opción, 2019)
Thematic analysis refers to examining the central idea that controls the entire literary piece. “The theme can take the form of a brief and meaningful insight or a comprehensive vision of life; it may be a single idea such as ‘progress’ (in many Victorian works).The theme may also be a more complicated doctrine, such as Milton’s theme in Paradise Lost, ‘to justify the ways of God to men’” (“Literary Terms,” 2006, para. T). Laurie Halse Anderson tends to focus on the themes of quest for identity and self- reclaiming in Speak. Theme is an effective way to analyze the author’s perceptions or points about life. Over the years, Anderson develops a voice through her works by finding creative ways to express her desires for independence. In this paper, the researcher shows Anderson’s ability in creating such an amazing work of fiction that discusses a special problem for teenager in high school in a sensitive way. The novel is not only interesting with a realistic depiction of real life but also it is a les- son for teens, parents and even teachers. In the depiction of teenage charac- ters, Anderson writes from knowledge and perspectives that are her own. She has made significant progress in literature to assert conventional roles of role models in the teenager’s life. Undeniably, Anderson writes not only to criticize the problem but also to solve it and construct the future.